Reliability Assessment of Multilevel Inverter for Modern Power System Applications - Singh S.; Dwivedi D.; Sarita K.; Saket R.K.; Sanjeevikumar P. (My University, 2025)
The rapid evolution of power electronics and digital control has enabled significant advancements in the design and application of multilevel inverters (MLI). As modern power systems (MPS) lean toward the integration of renewable energy sources (RES) and emphasize energy efficiency, and reliability of MLI becomes paramount. This chapter deals with the reliability assessment of various types of MLI and their relevance in the context of MPS applications. © 2024 by The Institute of Electrical and Electronics Engineers, Inc. All right reserved.